Utilization of folklore Sasak Doyan Neda as the material development of cultural tourism in Lombok: the study of antropholinguistic / Omir Erlaska - Erlaska, Omir (2019)
Folklore is one of the types of literature found in the communities in the various regions. Folklore can serve as means of information on the conditions of the communities of the area. It is included on the community the Sasak in Lombok island has one of the folklore which describes the condition of the community island of Lombok in the past namely folklore Hooked Neda.